Reviews (New blackfriars, 1970)
Book reviewed in this article: THE NEW TESTAMENT, ITS BACKGROUND, GROWTH AND CONTENT by bruce M. Metger Lutterworth Press, London BÀPTISM IN THE HOLY SPIRIT James D. G. Dunn SCHOOL FOR PRAYER, by Archbishop Antony bloom. Darton, Longman and Todd, London LEARNING TO PRAY, by Bernard Bro, O. P. Ecclessla Press, Shannon, ireland THE CLIMATE OF MONASTIC PRAYER, by Thomas Merton. Irish University Pres, Shannon THE EXPERIENCE OF PRAYER, by Sebastian Moore and Kevin Maguire. Darton, Longman and Todd, London MADLY SINGING IN THE MOUNTAINS, edited by Ivan Morris. George Allen d Unwin, London, 1970.